Pembinaan Agama Islam Terhadap Lanjut Usia di Panti Harapan Kita Kota Palembang - Hendriyenti, Hendriyenti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Islamic religious guidance is not only important to be given to children, but also for the elderly in order to achieve the degree of khusnul khotimah. The purpose of this study was to determine the development of Islam for the elderly at the Harapan Kita Panti, Palembang City. This study uses qualitative research methods, with research subjects namely the Chair and staff of the Harapan Kita Nursing Home in Palembang city as many as 17 people, 2 coaching staff, clients (elderly) as many as 48 people. Collecting data in this study using the method of observation, interviews and documentation. The results of the study indicate that Islamic religious development at the Harapan Kita Nursing Home in Palembang is a process of reintegrating the elderly. It is considered necessary because it is to help the condition of the elderly who experience various kinds of mental and spiritual disorders. All kinds of disturbances can only be overcome by drawing closer to Allah. Meanwhile, the process of one's approach to God needs to be nurtured. The activities that are part of the program in the context of fostering the Islamic religion at the Harapan Kita Nursing Home in Palembang city include recitation, congregational prayer and fasting. Thanks to the guidance of the Islamic religion at the Harapan Kita Nursing Home in the city of Palembang. Keywords: Development, Islam, Elderly